Enhancing Accounting-Based Entrepreneurial Capacity for Youth Creative MSMEs - Nugrahanti, Trinandari; Lanjarsih, Laela; Mutumamikam, Primadonna Ratna; Salim, Agus; Hanantijo, Djoko (TAAWUN, 2026)
This community service aims to enhance the capacity of accounting-based entrepreneurship among young creative MSME actors in Purwadana Village, East Telukjambe District, Karawang Regency, by improving financial recording skills, preparing simple financial statements, and making data-driven business decisions. The activity was carried out using a participatory approach, with stages of socialization, training, and mentoring for creative MSME actors. The material provided includes recording transactions, preparing simple income statements, managing cash flow, and separating business finances from personal finances. The results of the activity showed an increase in participants’ understanding and skills in business financial management. Participants began to record transactions regularly, compile simple income statements, separate business and personal finances, and use financial information to evaluate business performance and support decision-making. This program contributes to strengthening the capacity of accounting-based entrepreneurship and supporting the sustainability of creative MSMEs at the village level.